Appraisal of wild fig fruits for nutra-pharmaceutical and biological attributes - Ahmad, Naveed; Anwar, Farooq; Abbas, Ali; Shahid, Muhammad; Iqbal, Munawar; Al-Mijalli, Samiah H.; Iqbal, Shahid; Tian, Mengfei; Zhao, Chunjian; Nazir, Arif (Elsevier BV, 2023)
The fruits of wild fig, native to Soon valley of Pakistan, were appraised for phenolic compounds and high-value nutrients. These fruits were shade-dried and extracted with different solvents of varying polarity to recover a wide range of antioxidant components, where hydroxyethanol exhibited highest extraction yield of antioxidant compounds. Among others, hydroxyethanol-derived crude concentration extracts (CCEs) and phenolic rich fractions (PRFs) showed greater amount of total phenolic, flavonoids and superior biological properties. The fruits of tested fruits were found to possess potassium (11.34 g/kg) and calcium (4.19 g/kg) as major elements, glucose (5.63g/100g DW) as dominant natural sugar and acetic acid (2.40 mg/100 g of dry matter) as principal organic acid. There was a considerable (p < 0.05) variation in phenolic content and biological properties of various extracts recovered with different solvents. Furthermore, the biological properties of tested fruits were found to be significantly correlated with their intrinsic total phenolic content (TPC) and total flavonoid content (TFC). Based upon the findings of present study, the fruits of wild fig could be treated as promising source of beneficial nutrients and potent phenolic components for their applications in the development of nutrapharmaceuticals.